Challenging traditional masculinity: minority norms and the reimagining of male gender roles - Islam Borinca; Theofilos Gkinopoulos (Social Influence, 2025)
Rigid traditional masculinity norms are linked to emotional suppression and relational strain, particularly among heterosexual men. This research examined whether sexual orientation shapes masculinity-related attitudes and whether exposure to sexual minority norms can shift them. In Study 1 (N = 250, U.S.), heterosexual men endorsed traditional masculinity more strongly and reported lower emotional vulnerability than gay men. These differences were mediated by less embracement of non-traditional domestic and relational roles. In Study 2 (N = 293, U.K.), heterosexual men exposed to narratives of gay men embracing non-traditional roles showed reduced masculinity endorsement and increased emotional vulnerability. Perceptions of generational shifts remained high across conditions. Sexual minority norms can thus promote more inclusive masculinities through minority influence.